Document supply services enhance access to information resources in Uganda - Musoke, Maria G.N. (Interlending & document supply, 2009)
Purpose – This paper aims to highlight the development of document supply services in Uganda, and Makerere University in particular, and the role they have played in increasing access to and use of information resources. Design/methodology/approach – The paper presents DSS at different levels and in different formats. Two major levels are discussed: The first is from international sources through collaborations/partnerships with Makerere University to benefit the Makerere University community; while the second type is within Uganda – from Makerere University to benefit other universities, rural institutions and practitioners/extension workers. Findings – Improved document delivery service has played an important role in resource sharing, which has led to increased access and usage of information resources in Uganda Originality/value – The paper is of value to librarians and other practising information professionals as well as library school students who may need to develop document supply services to under-resourced areas and particularly remote regions.
Keywords: Uganda; Document delivery